Analisis Trend Bagi Pesalah Muda Yang Telah Menjalani Hukuman Perintah Khidmat Masyarakat Di Malaysia (A Trend Analysis Among Young Offenders Undergone Community Service Order In Malaysia) - Tharshini, A/P Sivabalan; Fauziah, Binti Ibrahim (The Malaysian Journal of Psychology (JPM), 2018)
This article attempts to present the trend among young offenders undergone Community Service Order (CSO) in Malaysia. An archival time series analysis approach was applied to identify the ethnicity, gender, type of crime and the total number of young offenders undergone CSO across Malaysia from 2009 until 2015. Relevant information was gathered after obtaining official statistic from the Department of Social Welfare Malaysia. In sum, a total number of 13,896 cases were reported in sixyear duration throughout Malaysia. The highest number of cases were recorded in Wilayah Persekutuan Kuala Lumpur (545 cases). Moreover, an overall number of 2,989 young offenders have successfully undergone CSO from 2009 until 2015. The resultant data also indicated that majority of male young offenders undergone CSO are Malays in ethnicity (67.79%) and most of them have involved in property-related crime (47%). As an overall impact, the study provided implications to the concerned parties and key personnel such as welfare officers, criminal justice authorities and policies makers to reinforce the implementation of a community-based approach to recuperate young offenders who have involved in criminal activities.